Management of deep space infections of the neck - Ciprian Venter; Alina Pantiș; Oana Vălenaș; Ildiko Sorban; Maria Domuța; Cristian Bălălău; Razvan V. Scaunasu; Bogdan Popescu (Journal of Mind and Medical Sciences)
Infections of the deep neck spaces often present a clinical challenge for the ENT surgeon. Management of these complex suppurations of the neck requires in fact a multidisciplinary approach due to possible complications like mediastinitis, septic shock and MSOF, life threatening bleeding and ICU management. The spread of infection from the primary site to other regions is possible through the lymphatic, arterial and venous vessels, or directly along the fasciae. There are several classifications for the etiology, pathogenic mechanism and site of evolution, the most frequently encountered clinical forms being peritonsillar abscess, retropharyngeal abscess, lateropharyngeal abscess, and the deep cervical abscess. All of these abscesses are suppurative complications of primary neck infections. Extensive inflammation and suppuration of the neck requires in most cases multiple incisions for drainage such that patients experience significant scarring of the neck. Along with the presence of the tracheostomy and nazo-gastric feeding tube, the aesthetic aspect of the neck surgery involves a high degree of psychological stress for the patients. As a conclusion and in line with literature data, patients must be fully informed about the technique and the outcome of the surgery so that they can provide informed consent since the pathology can be both life- threatening and mutilating.